INTERVENSI KOMUNITAS: STRATEGI PENANGGULANGAN BENCANA BERBASIS MASYARAKAT DI KABUPATEN DELI SERDANG - Ahmad Yaneri (GoAcademica Research dan Publishing, 2020)
The BPBD annual report of North Sumatera shows that almost every year at several points the area has experienced an increase in natural disasters, this has implications for the formation of disaster preparedness cadets (Tagana) in Deli Serdang Regency who act as the front guard in disaster management. Through a qualitative approach, this thesis was conducted to describe how community intervention applied by Tagana in Deli Serdang regency in managing natural disaster so that it creates self-community in solving the problems, particularly the alertness in preparation to face natural disaster. The research findings show that, implementation of community interventions by Tagana in disaster management in Deli Serdang has a maximum are because of several supporting factors such as the community participation and professional personnel in terms of disaster expertise. In addition, Tagana is also facing the obstacle factors in the implementation of community interventions such as the predisposition and the dependence on funding.